Impact of Agricultural Land Changes on Farmers’ Income in Cirasea Watershed, Bandung Regency, West Java - Teguh Husodo; Indri Wulandari; Oekan S Abdoellah; Martha Fani Cahyandito; Sya Sya Shanida (Research Centre of Inorganic Materials and Complexs, 2021)
Changes from agricultural land to non-agricultural land are continuously occurring, especially in areas adjacent to cities. Land changes from agricultural to non-agricultural land will eliminate crops’ hydrological function, impacting rivers, including the Cirasea River. Besides, changes in agricultural land have an impact on the resulting agricultural productivity and income. This study’s main objective is to determine land area changes, productivity, and farmers’ income in 2011 - 2018 in the Cirasea watershed. A literature study was applied to this study. Secondary data were obtained from the Central Bureau of Statistics of Ciparay, Ibun, Kertasari, Majalaya, Pacet, and Paseh Districts, Bandung Regency in Cirasea River Upstream. The study results showed an increase in land area, productivity, and agricultural income for vegetables (75%, 50%, and 68%, respectively) and rice field (16%, 0.32%, and 0.32%). In addition, there was a decrease in land area followed by a decrease in agricultural productivity and income for fruit commodities (-88%, -35%, -33%) and plantations (-97%, -1%, -1%). For eight years, farmers have relied on their income from vegetable commodities in Cirasea Watershed.